Tourism, the hotel industry at the time of the COVID-19 pandemic - Anna Ostrowska-Tryzno; Anna Pawlikowska-Piechotka (Sport i Turystyka, 2022)
The tourism industry is especially sensitive to a pandemic and other unexpected circumstances as natural disasters, war, terrorist attacks. Different types of crisis bring various consequences. In 2020 the outbreak of the COVID-19 disease and travel restrictions caused bruises to the tourism and hospitality industries. Hotel managers, hotel staff and their guests had to take a series of measures to deal with various challenges and face a new situation.